OPTIMALISASI HASIL BELAJAR MATEMATIKA DENGAN PEMBELAJARAN KOOPERATIF TIPE TGT BERBANTUAN WORDWALL DI SEKOLAH DASAR - Fitria Handayani; Ika Rahmawati; Fitria Sucianti (STKIP Subang, 2024)
The aims of this research is to improve students ability in the mathematics subject of sorting and comparing whole numbers in class IV through cooperative learning type TGT (Teams Games Tournament) assisted Wordwall. The research is classroom action research (PTK) which applies 2 cycles. To analyze the data, researcher using quantitative descriptive technique. Subjects of this research are 26 class IV students at SDN Dukuh Kupang V, consist of 12 are boy and 14 girls. The indicator for the success of this research is the percentage of completeness that students must achieve ≥75%. The results show that the learning outcomes in the pre-cycle were less than satisfactory and under the percentage of completeness, the average is 40.38 with a percentage of completeness is 19.23%. After being given action to implement TGT with Wordwall in cycle I, the average learning outcome was 58.46 and the percentage of 57.7%. On the cycle II the average student learning outcome was 77.31 with a completion percentage 80.8%. Based on the results of pre-cycle, cycle I, and cycle II, can be conclude that the value and percentage of students’ learning completion increased until reached the specified KKTP. It means, the implementation of cooperative learning type TGT assisted by Wordwall is success and give the maximum results.